Analysis of the Application of Salam and Istisna'a Contracts in Agricultural and Industrial Sector Financing at Bank Syariah Indonesia - Nurul Zahra Ismi Putri; Krisdiana Resi; Mohammad Syawal Fadillah; Andi Sinta Bella; Nadila Nadila; Hamida Ambas (Entrepreneurship, Management, and Business Research Journal, 2026)
This study examines the application of Salam and Istisna'a contracts in financing the agricultural and industrial sectors at Bank Syariah Indonesia. Salam is a forward-buying contract involving advance payment for goods delivered at a future date, whereas Istisna'a entails purchasing goods that are to be manufactured or ordered with advance or deferred payments. Employing a qualitative approach with a literature review method, this research analyzes various references concerning the implementation of both contracts within Indonesia's agricultural and industrial sectors. The findings indicate that the Salam contract facilitates essential production financing for farmers, yet it faces challenges such as commodity price fluctuations and weather uncertainty. Conversely, while the Istisna'a contract proves beneficial in the industrial sector for procuring raw materials or customized products, it encounters constraints regarding timely delivery and product quality. These challenges can be mitigated through more precise contractual agreements regarding pricing, product specifications, and delivery schedules. Furthermore, information technology can be utilized to monitor market prices and production processes to minimize uncertainty. This study provides insights into how Salam and Istisna'a contracts can be effectively implemented in the agricultural and industrial sectors, alongside solutions to enhance the successful application of both instruments in Islamic banking practices.